Pengaruh Kecerdasan Emosional, Tingkat Idealisme, Perilaku Belajar dan Locus of Control terhadap Tingkat Pemahaman Akuntansi Mahasiswa Strata Satu (S-1) Akuntansi pada Perguruan Tinggi di Kabupaten Banyumas - Dona Primasari (Jurnal Maksipreneur, 2016)
This study aims to examine the influence of emotional intelligence, the level of idealism, learning behavior and the locus of control of students to the understanding of accounting. The sample consists of accounting students in Banyumas District. Data analysis using SPSS. The results showed that the emotional intelligence, the level of idealism, and the locus of control students influence the understanding of accounting, while the behavior of learning proved not to affect the understanding of accounting.